Henry Kissinger - Wagner, Abraham R., author.
1 online resource.
Keywords: “This book reveals Henry Kissinger's realpolitik approach to U.S. foreign policy. Wagner tracks how Kissinger became an iconic figure in international relations that polarized opinion during 1969 to 1977, a critical and controversial period of American history.“